2002
DOI: 10.1095/biolreprod66.4.1068
|View full text |Cite
|
Sign up to set email alerts
|

Interval Between Preovulatory Surges of Luteinizing Hormone Increases Late in the Reproductive Period in Turkey Hens1

Abstract: In turkey hens, the egg production rate is relatively high early during a reproductive period, but declines as the period progresses. Among lines with different egg production potential, the interval between preovulatory surges of LH is the primary determinant of the egg production rate. The main objective of this study was to determine whether the decline in egg production rate late during an egg production period is also associated with a difference in the interval between LH preovulatory surges. A group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 45 publications
(90 reference statements)
2
9
1
Order By: Relevance
“…Also, no long-duration intersequence intervals (intervals Ͼ 30-34 h) ascribed to pauses between sequences [21] were observed in the present experiment. In a longitudinal study using the Egg line of turkeys [19], a slightly longer interval between LH surges (27.9 and 25.7 h, respectively) was found with constant lighting than with 14L:10D diurnal lighting.…”
Section: Hormonecontrasting
confidence: 79%
See 2 more Smart Citations
“…Also, no long-duration intersequence intervals (intervals Ͼ 30-34 h) ascribed to pauses between sequences [21] were observed in the present experiment. In a longitudinal study using the Egg line of turkeys [19], a slightly longer interval between LH surges (27.9 and 25.7 h, respectively) was found with constant lighting than with 14L:10D diurnal lighting.…”
Section: Hormonecontrasting
confidence: 79%
“…In a previous study with the Egg line of turkeys [21], LH surge amplitude declined further between 3 and 40 wk of egg production, but duration of surges did not change with progression of the reproductive period. Surges of LH are induced by surge secretion of GnRH in birds as in mammals [29].…”
Section: Hormonementioning
confidence: 60%
See 1 more Smart Citation
“…(Onagbesan et al, 2006). Furthermore, the influential role of LH on egg production was further elucidated by Liu et al (2002;2004) that the intervals between the LH surges are longer in broiler breeder and turkey hens with low egg production rates. In similar vein, the depressed laying rate observed during the non-breeding season was found to parallel low LH secretion and circulation in geese (Shi et al, 2007;Huang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that FSH secretion did not change with P 4 treatment, because levels of E 2 did not change during P 4 treatment or development of the PCOF syndrome in experiment 8. For laying hens late in the egg production period, the level of E 2 has been reported to decline [33]; thus, FSH secretion may also be lower at this time. In older hens, a lower rate of FSH secretion may lead to atresia of ovarian follicles during P 4 injection (experiments 2 and 6) instead of ovarian follicle maintenance (experiments 1, 3, 4, and 5) or development of the PCOF syndrome (experiments 7 and 8) subsequent to P 4 injection.…”
Section: Discussionmentioning
confidence: 96%